Advantages of STEAM Approach in Teaching Fine Arts - Xasanova Sitora Shuhrat qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
ANNOTATION: This article examines the advantages of applying the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach in teaching fine arts. It emphasizes how integrating artistic education with scientific and technological disciplines enhances creativity, problem-solving skills, and critical thinking among students. The study highlights that STEAM-based teaching fosters interdisciplinary learning, promotes innovation, and prepares learners for contemporary educational and professional challenges. Drawing on the research of S.A. Shovdirov and other pedagogical scholars, the article analyzes practical methods for implementing STEAM principles in fine arts lessons and explores the resulting cognitive, creative, and collaborative benefits for students.